2022
DOI: 10.1088/2051-672x/ac9150
|View full text |Cite
|
Sign up to set email alerts
|

A study on in-vitro behaviour of stainless steel 316L subjected to rotational magnetorheological abrasive flow finishing process

Abstract: In Rotational Magnetorheological Abrasive Flow Finishing (R-MRAFF) process, Magnetic Field Intensity (MFI) is the primary factor for the formation of ferrous chains which is responsible for finishing. Changing the pole distance between magnets to achieve a difference in MFI values will alter the strength of the ferrous chains. In this study, three different MFI values such as 0.34, 0.36, and 0.40 Tesla were chosen for finishing on Stainless Steel 316L (SS 316L). Surface wettability, bio-corrosion, and hemocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…GFRP with banana fibre has an average material removal rate of 0.2932 mm3/min. The GFRP with banana fibre has maximum and minimum observed values of 0.4516 mm3/min and 0.1625 mm3/min, respectively [23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 95%
“…GFRP with banana fibre has an average material removal rate of 0.2932 mm3/min. The GFRP with banana fibre has maximum and minimum observed values of 0.4516 mm3/min and 0.1625 mm3/min, respectively [23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 95%
“…Speed of the spindle (m/min) Different reinforcing ratios of fly ash to AL6061 were observed to affect the surface roughness of the fly ash reinforced AL6061 composite [16]. Using the Taguchi approach, the surface roughness of new Al/fly ash composites was determined in this study [17][18][19][20][21][22]. No contrary study analysis was found in the surface roughness findings.…”
Section: Trailmentioning
confidence: 92%
“…No contrary study analysis was found in the surface roughness findings. The limitations are the tool wear and the effect of coolant were not focussed in aerospace AA7475 metal matrix composite applications [23][24][25][26][27][28][29][30]. In the future, research work can be expanded for usage of different types of milling cutter tools and the addition of various ceramics such as Al2O3, TiB2 and TiO2 in Aluminium should be done to check the Surface Roughness and machining parameters.…”
Section: Trailmentioning
confidence: 99%
“…Journal of Physics: Conference Series 2484 (2023) 012024 [22][23][24][25][26][27][28][29][30]. According to the ANOVA table for the SN ratio of GFRP, GFRP combined fresh Grass powder, and GFRP blended banana fibre, the drill diameter was the most crucial element, followed by cutting speed and feed rate.…”
Section: Icmmt-22mentioning
confidence: 99%